In vitro toxicity of TiO2 nanoparticles immobilized on clay to human hepatic cells - Bessa, M.J. (2017)
Objective: Evaluate in vitro toxicity of TiO2 nanoparticles immobilized on clay (C-TiO2) in a hepatocellular carcinoma human cell line (HepG2) as well as of its single elements.